DEVELOPMENT OF THE INTERNAL CONTROL SYSTEM IN SPECIALIZED SEED-PRODUCING FARMS - Bozorboeva Zarnigor Gulmirza qizi (Scholar Express Journals, 2025)
This article examines the development of an effective internal control system in specialised seed-producing farms. It analyses the issues of ensuring the transparency and accuracy of accounting information related to the cost formation of seed production and storage. The study proposes improvements to existing documentation and the introduction of new forms that ensure compliance with international accounting standards, thereby enhancing internal control and management efficiency
Keywords: Seeds; accounting; seed production; documentation